2013
DOI: 10.1161/circresaha.112.300735
|View full text |Cite
|
Sign up to set email alerts
|

AKT2 Confers Protection Against Aortic Aneurysms and Dissections

Abstract: Rationale Aortic aneurysm and dissection (AAD) are major diseases of the adult aorta caused by progressive medial degeneration of the aortic wall. Although the overproduction of destructive factors promotes tissue damage and disease progression, the role of protective pathways is unknown. Objective In this study, we examined the role of AKT2 in protecting the aorta from developing AAD. Methods and Results AKT2 and phospho-AKT levels were significantly downregulated in human thoracic AAD tissues, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
80
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 60 publications
6
80
2
1
Order By: Relevance
“…PI3Kγ, the molecule upstream of Akt, was proved to inhibit the expression and activity of MMP-2 and MT1-MMP induced by biomechanical stress (Guo et al 2010). Akt2 inhibited MMP-9 expression while stimulated TIMP-1 expression by enhancing phosphorylation of FoxO1 in cultured VSMCs (Shen et al 2013). Furthermore, they found that there were FoxO1a binding sites in MMP-9 and TIMP-1 promoters.…”
Section: Discussionmentioning
confidence: 97%
“…PI3Kγ, the molecule upstream of Akt, was proved to inhibit the expression and activity of MMP-2 and MT1-MMP induced by biomechanical stress (Guo et al 2010). Akt2 inhibited MMP-9 expression while stimulated TIMP-1 expression by enhancing phosphorylation of FoxO1 in cultured VSMCs (Shen et al 2013). Furthermore, they found that there were FoxO1a binding sites in MMP-9 and TIMP-1 promoters.…”
Section: Discussionmentioning
confidence: 97%
“…11,20,21 In BAPN/Ang II-treated mice, neutrophils infiltrate the aortic intima, invariably triggering aortic dissection via metalloproteinase-9 production. 12 The sequence of events leading to aortic dissection in this model may well reflect those that underly a similar aortic pathology in humans.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, the expression and activation of Akt were prohibited in human aortic aneurysmal tissues and knockout of Akt-2 deteriorated Ang II-induced AAA. 22 NF-κB is an important transcriptional factor that mediates the expression of many proinflammatory cytokines and can be activated by Ang II. In this study, mediating these effects.…”
Section: Discussionmentioning
confidence: 99%